Artificial intelligence is watching you at work: digital suveillance, employee monitoring, and regulatory issues in the EU context. - Aloisi, Antonio; Gramano, Elena (University of Illinois Press, 2019)
By affecting activities in both traditional and modern industries, countless invasive devices constitute a burgeoning terrain for new forms of monitoring assisted by artificial intelligence and algorithms; these range from badges to tablets, from wearables to exoskeletons, from collaborative software to virtual personal assistant, from computer networks to face recognition systems. From a legal perspective, these tools constantly collect, produce, share and combine data that may be used by the employer for all the many different reasons, thus leading to a “genetic variation” of the organizational, monitoring and disciplinary prerogative, considered as the core of the employment contract. When it comes to recruiting, managing, and vetting the workforce, AI applications can be considered as an effective combination of big data analytics and algorithmic governance. Only recently, have international, European and domestic institutions started considering how to update existing regulation in order to face these complex and far-reaching challenges. This article assesses the effects of AI application on the employment relationship, with a view to understanding how social and legal institutions act, react or adapt to a potential experience of unprecedented digital surveillance in the workplace, entrenching command-and-control relationships between management and workers. The paper is organized as follows. After describing the new arenas of workplace surveillance, we provide a comprehensive conceptualization of AI application. Section 2 explores the latest generation of digital devices, understood in their broadest definition encompassing both physical supports as well as intangible tools. In many cases, AI prevents accidents caused by human error or reduce the hazard (or even the burden) of routine and menial activities. On the other hand, these software and devices create an effective, invasive and elusive system of watchfulness increasing conformity and promoting docility. Section 3 describes how the EU has set the tone globally in the regulation of privacy and data protection. In particular, we scrutinize the new GDPR thoroughly. One concern on its effectiveness revolves around the limits on the automated decision-making processes (Art. 22). Section 4 describes how some European civil law systems deal with the regulation of surveillance of workers. The cases of France, Germany and Italy are analyzed by stressing the common elements and loopholes. Section 5 assesses some conclusions by verifying whether the current regulations are suitable to cope with the adoption of AI at work.
Keywords: Artificial intelligence; GDPR; Surveillance; Monitoring; Data protection; Employment; 12 Matemáticas::1203 Ciencia de los ordenadores ::1203.04 Inteligencia artificial; ODS 8 - Trabajo decente y crecimiento económico